Hearing status among smokers using extended high frequency pure tone audiometry (EHFPTA) and distortional product of otoacoustic emissions (DPOAE) - Ali, Atiyah; Ismail, Noraidah; Ismail, Noor Afzarini Hasnita (Majmuah Enterprise, 2019)
Objective: The purpose of this study is to measure the hearing level among smokers using high frequency sensitive testing which are extended high frequency Pure Tone Audiometry (EHFPTA) and Distortional Product of Otoacoustics Emissions (DPOAE). This study focuses on four specific objectives which determine the hearing level of smokers at high frequencies, identifying amplitude of DPOAE in measuring damage level of hearing cell in cochlea, correlating the smoking duration on hearing and lastly, smoking quantity per day effects on hearing. Methods: 30 subjects participated in this study whereby they were divided into testing groups (smokers) and control groups (non-smokers). Results: The result of this study found that there are elevation of threshold at 16 KHz, 18 KHz and 20 KHz among smokers compared to non-smokers depending on duration (years) and quantity of smoking (per day). The higher the number of cigarettes being smoked per day, and the longer duration of smoking, the higher the potential of getting hearing loss. This study result also found that the longer the duration of smoking (years), it also may increase the chance of hearing elevation especially at high frequency. Mean amplitudes of DPOAE among smokers was significantly low compared to non-smokers except on 1.5 KHz and 8 KHz. Conclusion: This study implies that the damaging effects of smoking tend to reduce the hearing sensitivity at extended high frequency first which later can be progressively affected on other frequency range of hearing.